Effects of different volumes of ovariectomy on fertility and offspring development of rats - Yang, Yu; Ruan, Xiangyan; Cheng, Jiaojiao; Xu, Xin; Mueck, Alfred O. (Frontiers in Endocrinology, 2023)
The purpose of this study was to explore the effect of removal of different volumes of ovarian tissue on fertility and offspring development of SD rats.Methods: SD rats were randomly divided into 6 groups according to different volumes of ovariectomy:(1) Sham group (n=6), non-ovariectomized; (2) 25%-OVX group (n=6), with half of the left ovary excised; (3) 50%-OVX group(n=5), with the left ovary excised; (4) 75%-OVX group (n=5), with the left ovary and half of the right ovary excised; (5) 87.5%-OVX group(n=6), with the left ovary and three quarters of the right ovary excised; (6)100%-OVX group(n=6), with bilateral ovaries excised. These female rats(F0) were mated with healthy male rats one and four months after the surgery, and the offspring of F0 rats were named F1 1mon and F1 4mon , respectively. The number of days from mating to delivery and number of live cubs were recorded. At postnatal day 21(P21), the body weight, length and anogenital distance (AGD) of the cubs were measured.Results: There were no differences in the number of live cubs between 25%-OVX, 50%-OVX and sham groups. Rats in the 87.5%-OVX group did not give birth at 1 month and 4 months after the operation. When compared with the sham group, the body weight and length of F1 1mon at P21 were increased in 25%-OVX group and 50%-OVX group. However, after the second delivery, we controlled each mother's lactation to no more than eight pups. As a result, there were no differences in the body weight, length and AGD of F1 4mon among the three groups.Removal of less than 50% of the ovaries did not affect the fertility of rats and offspring development of rats.